Call me when you grow up: Firms' age, size, and IPO performance across sectors - Smadar Siev; Mahmoud Qadan (Journal of Risk and Financial Management, 2022)
We provide a fresh look at the performance of the stock prices of firms that launched an IPO between 2009 and 2019 and assess the role of their size, age and sector in affecting future performance. We utilize data about 1611 IPOs spanning 11 economic sectors using the event study method. We provide evidence that a firm's size and age do act as predictors for its price evolution in the future. In addition, there is a significant variation in the long-term performance between sectors and between small and large firms within each sector. Furthermore, there is a clear tendency of firms from sectors such as healthcare and technology to go public at a relatively younger age than other sectors. The results have implications for asset pricing and are useful for investors involved in IPOs.
Keywords: G11; G14; G17; 650; IPO; asset pricing; size; underperformance